Deaf Children's Engagement with American Sign Language-English Bilingual Storybook Apps. (12th October 2022) - Herzig, Melissa; Allen, Thomas E
Abstract: Design features of American Sign Language (ASL)-English bilingual storybook apps on the tablet computers, based on learning research, are intended to facilitate independent and interactive learning of English print literacy and of ASL skill among young learners. In 2013, the Science of Learning Center on Visual Language and Visual Learning introduced the first in a series of storybook apps for the iPad based on literacy and reading research. The current study, employing a sample of signing deaf children examined children's self-motivated engagement with the various design features presented in the earliest of the apps, The Baobab, and analyzed the relationships of engagement with ASL skill and age of first exposure to ASL, ASL narrative ability, and grade-appropriate English reading ability. Results indicated a robust level of engagement with the app, and a relationship between app pages specifically targeting reading and early exposure and skill levels in ASL. No evidence of relationships between narrative and vocabulary skills and app reading engagement was found. Topics for future research, and strategies for app improvement are discussed.